Cooperation Institutions (LKS) Bipartite Effectiveness in Efforts to Prevent Industrial Relationship Disputes of Companies in Ternate - Erwin Ismanto; Husen Alting; Rusdin Alauddin (Syntax Corporation Indonesia, 2022)
Effectiveness of cooperative institutions (LKS) bipartite in an effort to prevent industrial relations disputes in companies in Ternate City,The purpose of this research is to examineThe role of bipartite cooperation institutions (LKS) in the prevention of industrial relations disputes in companies, as well as the effectiveness of the establishment of bipartite cooperation institutions (LKS) in companies in Ternate City.The research method used is qualitative with a case study approach and data is collected through in-depth interviews with employers, workers/labourers, trade unions/labor unions and Industrial Relations Mediator Employees both in the regions and at the Ministry of Manpower. Some of the findings obtained from this study indicate thatIn the provisions of labor legislation, a bipartite work forum will refer to a communication and consultation forum to make careful considerations on matters relating to industrial relations in a company, where the members consist of employers/entrepreneurs and workers/laborers. or representatives of Workers/Labourers' organizations.